The Effects of Body Mass Index on Postoperative Complications in Patients Undergoing Autologous Free Flap Breast Reconstruction - Garoosi, Kassra; Yoon, YooJin; Winocour, Julian; Mathes, David W.; Kaoutzanis, Christodoulos (Journal of Reconstructive Microsurgery, 2024)
Background The prevalence of obesity in the United States exceeds 40%, yet perioperative effects of higher body mass index (BMI) in autologous breast reconstruction remain poorly studied. The purpose of this study was to investigate BMI's impact on postop complications in abdominal and gluteal-based autologous breast reconstruction.Methods We conducted a retrospective study using TriNetX, a health care database containing de-identified data from more than 250 million patients. Patients undergoing autologous breast reconstruction were identified by Current Procedural Terminology codes. Four cohorts were established by BMI class: <24.99, 25 to 29.99, 30 to 34.99, and 35 to 39.99 kg/m2. Outcomes of interest were defined by International Classification of Diseases, Tenth Revision (ICD-10) codes. A two-sample t-test was performed to compare incidence of postoperative complications between cohorts within 3 months of surgery. Patients with a BMI < 24.99 kg/m2 served as the control. Cohorts were balanced on age, race, and ethnicity.Results We identified 8,791 patients who underwent autologous breast reconstruction. Of those, 1,143 had a BMI < 24.99 kg/m2, 1,867 had a BMI of 25 to 29.99 kg/m2, 1,396 had a BMI of 30 to 34.99 kg/m2, and 559 had a BMI of 35 to 39.99 kg/m2. Patients with a BMI of 25 to 29.99 kg/m2 had a significantly increased risk of cellulitis. Patients with a BMI of 30 to 34.99 and 35 to 39.99 kg/m2 had a significantly increased risk of cellulitis, surgical site infection, need for debridement, wound dehiscence, and flap failure.Conclusion Our study illustrates that there is an increased risk of postoperative complications associated with higher BMI classes. Understanding these data are imperative for providers to adequately stratify patients and guide the procedural decision-making.
Keywords: breast reconstruction; free flap reconstruction; postoperative complications; body mass index